Holy Terror!: Islamophobia and Intermediality in Frank Miller’s Graphic Novel - Frank Mehring (European Journal of American Studies, 2020)
The graphic artist Frank Miller represents an innovative force in the field of graphic novels who pushes the medium into new territories. One such territory is Islamophobia and terrorism in his graphic novel Holy Terror (2011). This article explores how Islamophobia has been mediated and how media systems of the twenty-first century forge Islamophobia into new shapes asking: How does Frank Miller’s aesthetics of silhouetted bodies reframe Islamophobia in an interpictorial and intermedial discourse of images? To what extent do Miller’s graphic stylizations of Islamophobia remediate elements of his previous work on fictional (super)heroes and historical leaders from Batman to the 300 Spartans? I argue that Miller’s visual narrative participates in the Islamophobic discourse of American popular culture by appropriating a wide array of popular culture visual archives for a propagandistic call for Muslim “Othering.” Holy Terror references news media, films and television series, 9/11 photography, familiar comic book heroes, and, of course, Miller’s own oeuvre. Thus, the graphic novel represents what I conceive as a virtual agora where different media converge to negotiate public discourses on Islamophobia. I will turn to the medium of graphic novels to first reveal how Miller’s narratives and silhouette aesthetics of (super)heroes have become complicit with Islamophobic responses to the crisis of 9/11; second, to trace the discourse of Islamophobia in post-9/11 America in Miller’s work; and, third, to reveal how this discourse interlinks with the patriotic logic of the fight against terrorism.